Turning ZnO into an Efficient Energy Upconversion Material by Defect Engineering. (31st March 2014) - Stehr, Jan E.; Chen, Shula L.; Reddy, Nandanapalli Koteeswara; Tu, Charles W.; Chen, Weimin M.; Buyanova, Irina A.
<x xml:space="preserve">Abstract</x> Photon upconversion materials are attractive for a wide range of applications from medicine, biology, to photonics. Among them, ZnO is of particular interest owing to its outstanding combination of materials and physical properties. Though energy upconversion has been demonstrated in ZnO, the exact physical mechanism is still unknown, preventing control of the processes. Here, defects formed in bulk and nanostructured ZnO synthesized using standard growth techniques play a key role in promoting efficient energy upconversion via two‐step two‐photon absorption (TS‐TPA). From photoluminescence excitation of the anti‐Stokes emissions, the threshold energy of the TS‐TPA process is determined as being 2.10–2.14 eV in all studied ZnO materials irrespective of the employed growth techniques. This photo‐electron paramagnetic resonance studies show that this threshold closely matches the ionization energy of the zinc vacancy (a common grown‐in intrinsic defect in ZnO), thereby identifying the zinc vacancy as being the dominant defect responsible for the observed efficient energy upconversion. The upconversion is found to persist even at a low excitation density, making it attractive for photonic and photovoltaic applications.